Effectiveness and safety of implantable loop recorder and clinical utility of remote monitoring in patients with unexplained, recurrent, traumatic syncope. (2nd January 2023) - Palmisano, Pietro; Guerra, Federico; Aspromonte, Vittorio; Dell'Era, Gabriele; Pellegrino, Pier Luigi; Laffi, Mattia; Uran, Carlo; De Bonis, Silvana; Accogli, Michele; Dello Russo, Antonio; Patti, Giuseppe; Santoro, Francesco; et al.
ABSTRACT: Background: Implantable loop recorder (ILR) is still underutilized in clinical practice, especially in the setting of elderly patients with recurrent, traumatic, unexplained syncope. Data on the actual risk of traumatic syncopal recurrence during ILR monitoring in this specific patient setting are lacking. Research design and methods: Prospective, multicentre registry enrolling consecutive patients undergoing ILR insertion for unexplained, recurrent, traumatic syncope. In a proportion of enrolled patients, remote monitoring (RM) was used for device follow-up. The risk of traumatic and non-traumatic syncopal recurrences during ILR observation were prospectively assessed. Results: A total of 483 consecutive patients (68±14 years, 59% male) were enrolled. During a median follow-up of 18 months, a final diagnosis was reached in 270 patients (55.9%). The risk of syncopal and traumatic syncopal recurrence was of 26.5 and 9.3%, respectively. RM significantly reduced the time to diagnosis (19.7±10.3 vs. 22.1±10.8 months; p=0.015) and was associated with a significant reduction in the risk of syncope recurrence of 48% (p<0.001), and of traumatic syncope recurrence of 49% (p=0.018). Conclusions: ILR monitoring is effective and safe in patients with unexplained, recurrent, traumatic syncope. RM reduces the time to diagnosis and significantly reduces the risk of traumatic and non-traumatic syncopal relapses.